2021
DOI: 10.3390/ijerph182312782
|View full text |Cite
|
Sign up to set email alerts
|

Health Behaviors of Austrian Secondary Level Pupils at a Glance: First Results of the From Science 2 School Study Focusing on Sports Linked to Mixed, Vegetarian, and Vegan Diets

Abstract: Attaining healthy behaviors is essential at any life stage, particularly childhood, due to the strong link between children’s lifestyle and the subsequent adult state of health. This multidisciplinary study aimed to assess lifestyle behaviors of Austrian pupils of secondary schools I and II, with a specific focus on PA habits and diet types based on a large sample. In total, 8845 children/adolescents participated in the short standardized online survey on relevant health-related aspects nationwide. Valid and c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
2

Relationship

3
6

Authors

Journals

citations
Cited by 16 publications
(19 citation statements)
references
References 61 publications
3
11
0
Order By: Relevance
“…Bi et al (2019) demonstrated that overweight or obesity was positively related to low physical activity during adolescence [ 41 ]. In the study of Wirnitzer et al (2021), children involved in sports activities showed a more favorable body mass compared to not involved ones [ 42 ]. Hilpert et al (2017) showed that a low level of physical activity was the key factor affecting overweight and obesity in children [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…Bi et al (2019) demonstrated that overweight or obesity was positively related to low physical activity during adolescence [ 41 ]. In the study of Wirnitzer et al (2021), children involved in sports activities showed a more favorable body mass compared to not involved ones [ 42 ]. Hilpert et al (2017) showed that a low level of physical activity was the key factor affecting overweight and obesity in children [ 43 ].…”
Section: Discussionmentioning
confidence: 99%
“…To date, only a limited number of reports focusing on the health of teachers [ 39 , 40 , 41 , 42 ] and school managers [ 43 , 44 ] exist, mostly with a major focus on mental health and stress management considering the school environment. There is a gap in the literature on the association between exercise behaviors and diet types (especially vegetarian, vegan) in the school context, except for one current report from our laboratory on secondary pupils [ 45 ]. Therefore, the present study aimed to examine the lifestyle behaviors of a large group of Austrian teachers and school principals at secondary levels I and II with a first glance not only to provide descriptive epidemiological data but a specific focus on “PA/sport participation” and “diet type” subgroups to identify potential associations.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, school settings are well controlled regarding age groups (school level), state educational mandates/national curricula, and standardized teacher education at the tertiary level (University/College) ( 98 , 136 ). Concerning any future sustainable health solution, the central prerequisite is a health-promoting school environment ( 6 , 19 , 47 , 137 141 ). Therefore, health initiatives that exclude school settings are doomed to fail ( 48 , 49 , 142 ).…”
Section: Discussionmentioning
confidence: 99%
“…Although low BMI does not help determine whether an individual might be predisposed to chronic disease, a high BMI almost always does indicate such a predisposition ( 159 ). The characteristics of plant foods (low energy, high density of fiber, and nutrients) ( 16 , 76 , 83 , 150 ), however, do not seem to be the only reason for a healthier BMI in vegan/vegetarian populations since data indicate that those who follow plant-based diets may have other healthy lifestyle habits in addition, such as higher engagement in sports and exercise ( 76 , 141 , 160 ). Therefore, based on scientific evidence available, vegan adults may have the lowest risk for becoming overweight/obese as a risk factor of NCDs since they were most often reported within healthy BMI categories and thus at lower risk for developing NCDs ( 76 ).…”
Section: Discussionmentioning
confidence: 99%